If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30 + 3x = 6 Solving -30 + 3x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + 3x = 6 + 30 Combine like terms: -30 + 30 = 0 0 + 3x = 6 + 30 3x = 6 + 30 Combine like terms: 6 + 30 = 36 3x = 36 Divide each side by '3'. x = 12 Simplifying x = 12
| 15y^2-15t-30=0 | | (0.1x^8)(0.3x^3)= | | 4x-(-10)=-22 | | 4x+9=3x-12 | | 5x-(-10)=-35 | | z^2+12z+5=0 | | -3x^2+4x+2=0 | | 8R^2-24R=O | | lnx=7 | | 7x-9y=5 | | -30x^2+9x+12=0 | | 7u+4v=-14 | | V=cqt | | X+3.1=6.8 | | 3x^2+12x+13=0 | | -(8y+2)-(-7Y-3)=1 | | 7x^2-8=-3 | | 5(3x+2)-4= | | -32-12x=2x+8 | | 3x^2-14x-56=0 | | 3(n-5)=8+4n | | 0=x^2-5x+14 | | 0=x^2-x+5 | | 50*2+150*2= | | x(2+5x)=0 | | 20*15*8= | | 0+x^2=2x-8 | | 42*3*4= | | 42*11*10= | | 6*36*6= | | -16=8(6q-2) | | 48*8= |